Peculiarities of development of higher mental functions in athletes - Strelkov, V. I.; Mironova, O. I.; Romanova, A. V.; Trubnikov, V. V. (Theory and Practice of Physical Culture, 2017)
Abstract. As of today, pre-contest mental conditioning of Russian athletes is still the weakest aspect of their sports activity. The article presents the results of the study of the domestic athletes` higher mental functions dynamics over the academic year. Subject to the study were sports class graduates of comprehensive school, team coaches in various fields, and future psychologists. The following research methods were used: estimation of the short-term visual memory span by means of the "Mnemotest" block as part of the microprocessor hardware complex for psychophysiological testing; determination of the attention span using Gorbov-Schulte tables; Torrance test for creative thinking; "Raven's Progressive Matrices" E-IQ test. The experimental data indicate that it is imagination that undergoes the most significant transformation as the most sophisticated tool of mental conditioning. Higher mental functions are activated under the influence of the idea, which, being planted in the mental training process, acts as a subject-substitute for the acquired during sports training.